Organic matter enrichment in the Whittard Channel; its origin and possible effects on benthic megafauna. (August 2015) - Amaro, Teresa; de Stigter, Henko; Lavaleye, Marc; Duineveld, Gerard
Abstract: The Whittard Canyon (NE Atlantic) is one of the largest canyon systems on the northern Bay of Biscay margin. It likely receives a high input of organic matter from the productive overlying surface waters, and part of this organic matter may eventually be transferred down the canyon into the Whittard Channel extending from the canyon mouth onto the Biscay Abyssal Plain. To establish if substantial transport of organic matter takes place from the canyon into the deep-sea channel we: (1) deployed a benthic lander in the Whittard Channel for a period of one year to measure near-bottom particulate matter transport and deposition rates; (2) collected surface sediment samples from the Whittard Channel and adjacent areas to assess possible organic matter enrichment in the channel (3) surveyed transects across the channel and adjacent areas with towed video camera to assess distribution of benthic megafauna potentially indicating enhanced flux of fresh organic material. The video surveys revealed massive occurrence of elpidiid holothurians in the proximal Whittard Channel, whilst only low numbers were counted further down the channel and on areas adjacent to the channel. We speculate that these deposit-feeding holothurians were attracted by the elevated content of relatively fresh organic matter in surface sediments of the proximal channel, as indicated by analysis of the surface sediment samples. Yet, whilst we expected that organic matter enrichment in the channel could be attributed to down-canyon transport through the Whittard Canyon, this could not be confirmed by data recorded by the benthic lander. During most of the 1-year deployment period, the net near-bottom currents and suspended particulate matter transport was directed in up-channel direction. During two sediment-gravity flow events recorded in March and July 2011, most likely originating from the Whittard Canyon, substantial deposition of particulate matter did occur in the Whittard Channel. However, the material deposited during those events consisted largely of inorganic sediment and was relatively poor in fresh organic material, and hence could not have substantially contributed to the organic matter enrichment observed in the channel. The highest deposition flux of fresh organic matter, recorded in May 2011, was not associated with any down-channel flow and more likely was derived from local settling of phytodetritus produced during the spring phytoplankton bloom. Based on our observations we infer that the organic enrichment observed in the proximal Whittard Channel is due to redistribution of phytodetritus by bottom currents, and accumulation of this material in the topographic depression formed by the Whittard Channel. The mobility of the elpidiid holothurians allows them to exploit these localised food sources. Highlights: Camera surveys and multicore sampling of the Whittard Channel and the adjacent abyssal plain revealed high numbers of elpidiid holothurians and elevated phytopigment concentrations inside the Whittard Channel suggesting that the Channel may act as conduit for OM. The benthic lander in the Whittard Canyon recorded several mass sediment transport events. Analysis of the current direction, concentration and freshness of the organic matter in the sediment however, exclude that these flows supply the fresh organic matter that we found in the Channel. Elevated concentration of phytopigments in the Whittard Channel result from local deposition possibly followed by redistribution and accumulation inside the deeper Channel. Accumulated labile OM in the channel could well explain higher abundances of elpidiid holothurians, but the mechanism behind these aggregations (combination of scent, movement) is obscure. The mobility of the elpidiid holothurians allows them to exploit these patchy food sources and are linked with the high densities observed.